1970
DOI: 10.1039/c2970001267a
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the carbanion formed in the hydrolysis of phosphonium salts

Abstract: Kinetic isotope effects, k,/k,, of ca. 1.2 observed in the protonation of carbanions formed in phosphonium salt hydrolysis show that these carbanions are not free in the rate-determining transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…10,11 The PIE decreases below this maximum value for either thermodynamically favorable or unfavorable proton-transfer reactions. [11][12][13] PIEs of 1.0 for nonenzymatic reactions in aqueous solution are almost never observed [14][15][16][17][18] but are possible for a complex reaction mechanism where proton transfer occurs after the step that determines the yields of hydrogen-and deuterium-labeled reaction products. In this case the deuterium enrichment of product will be determined by the initial deuterium enrichment of the catalytic acid.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The PIE decreases below this maximum value for either thermodynamically favorable or unfavorable proton-transfer reactions. [11][12][13] PIEs of 1.0 for nonenzymatic reactions in aqueous solution are almost never observed [14][15][16][17][18] but are possible for a complex reaction mechanism where proton transfer occurs after the step that determines the yields of hydrogen-and deuterium-labeled reaction products. In this case the deuterium enrichment of product will be determined by the initial deuterium enrichment of the catalytic acid.…”
Section: Introductionmentioning
confidence: 99%
“…This is deprotonated by hydroxide to give an oxyanionic phosphorane, which expels a carbanion (probably protonated in the process of its expulsion) to give phosphine oxide and alkane or arene. 27 Largely on the basis that ylide hydrolysis gives the same products as phosphonium salt hydrolysis, 15 it has generally been concluded that ylide hydrolysis proceeds by the same mechanism with one extra (initial) step -protonation of the ylide by water to give phosphonium hydroxide. 10,28,29 The existence of an intermediate in these reactions is a necessity in view of the kinetic order of the reaction (& in particular that it is 2nd order in hydroxide).…”
mentioning
confidence: 99%
“…This phosphonium cation can react with methoxide to form a five-coordinate phosphorane, which itself can then react with methoxide to form phosphine oxide by rupture of one of the phosphorus-carbon bonds of the original phosphonium cation. The PeC bond that is ruptured is known to be that which gives the more stable anion [19]. In this case, the allyl anion is displaced preferentially to the phenyl anion, so the phosphine oxide formed would be expected to be triarylphosphine oxide.…”
Section: Decomposition Of Phosphines During Telomerizationmentioning
confidence: 96%